Towards A Circular Energy Economy: Cross-Sector Successes in Brazil and India - Brown, Hillary (Consilience, 2018)
A new paradigm for energy production is one that emulates the closed-loop circular systems of natural ecosystems. At once holistic, economical, and equitable, energy production based upon reciprocities with other sectors (e.g. telecommunications, water, sanitation, and waste management) can leverage synergies and provide multiple co-benefits. With avoidance of fossil fuels, less pollution, and reduced throughput of matter and energy, such a circular energy economy offers a model for critical electricity provision for the next 2 billion people in emerging economies—both those moving to cities and particularly those who remain in rural poverty. Three exemplary cases, one in India and two in Brazil, reveal the efficacy of renewable power created through cooperative, cross-sector initiatives that also yield economic and social benefits. The first, methane recovery in Belo Horizonte, Brazil, illustrates the potential for closed-loop use of an otherwise wasted energy source in rapidly urbanizing settlements. In the second case, Omnigrid Micropower Company leveraged affordable electricity for some of India’s poorest rural citizens by combining the electricity demand from the telecommunications sector to support the economical construction of small- to mid-size solar power plants. Lastly, Brazil and Paraguay’s Itaipu Binacional, developer of the world’s largest generator of renewable power, addressed the pollution of its reservoir from agricultural waste by establishing a rural waste-to-energy program that electrified 2,200 households. Moving beyond conventional, mono-sectoral approaches to energy delivery, these alternative, circular strategies for power production are solving energy poverty. As blended, multi-functional systems, they have also fostered job creation, allowing for economic growth while suppressing carbon emissions.